National Scientific Misconduct Policies in Argentina: Two Definitions of Research Misconduct - Bianchini, Alahi Dana (2018)
In “An International Study of Research Misconduct Policies”, Resnik et al. count Argentina in the list of countries without national research misconduct policies. In this paper, we clarify that Argentina has national policies of research misconduct and present the research misconduct definitions of two official science organisms: the National Scientific and Technical Research Council (CONICET) and the Ethics Committee of the Argentine Ministry of Science (MINCyT).